Tyrosinase inhibitory activity and physicochemical properties of microalgae extract (Spirulina platensis)-loaded nanostructured lipid carriers gel - Faizatun, Faizatun; Abdullah, Abdullah (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Microalgae (Spirulina platensis) belongs to the family Cyanobacteria contains phycocyanin which is efficacious as a tyrosinase inhibitor. The purpose of the study was to make gel of Nanostructured Lipid Carriers (NLC) from the Microalgae extract (Spirulina platensis). Extracts were made by maceration with 70% ethanol solvent and evaluation of the enzyme tyrosinase inhibitory activity. The extract was made by NLC with solvent evaporation method and characterized which included particle size, polydispersity index, zeta potential and Transmission Electron Microscope (TEM). NLC extract was made into gel preparations by adding gelling agent, and evaluation included organoleptic homogeneity, viscosity and flow properties, pH, and the enzyme tyrosinase inhibitory activity. The enzyme tyrosinase inhibitory activity of Microalgae extract (Spirulina platensis) with the result IC50 in the amount of 150.22 Âµg/mL. Five of NLC formulas was made based on the characterization obtained the best formula is NLC formula 2, which includes particle size of 119.6 nm, polydispersity index of 0.356, zeta potential of -37.8 mV, and spherical shape. The evaluation results of the gel were semi-solid, brown, typical smell, homogeneous, viscosity of 19500 cPs, plastic thixotropic flow properties, and pH 5.06. The enzyme tyrosinase inhibitory activity of NLC gel Microalgae extract (Spirulina platensis) with the result IC50 in the amount of 173.38 Âµg/mL. It can be formulated into a physically and chemically stable gel preparation and has activity as a tyrosinase inhibitor.